Equilibrium Provider Networks: Bargaining and Exclusion in Health Care Markets - Ho, Kate; Lee, Robin S. (American Economic Review, 2019)
We evaluate the consequences of narrow hospital networks in commercial health care markets. We develop a bargaining solution, "Nash- in-Nash with Threat of Replacement," that captures insurers' incentives to exclude, and combine it with California data and estimates from Ho and Lee (2017) to simulate equilibrium outcomes under social, consumer, and insurer- optimal networks. Private incentives to exclude generally exceed social incentives, as the insurer benefits from substantially lower negotiated hospital rates. Regulation prohibiting exclusion increases prices and premiums and lowers consumer welfare without significantly affecting social surplus. However, regulation may prevent harm to consumers living close to excluded hospitals.